Backpackers’ Utopianism in Alex Garland’s “THE BEACH” - Astuti, Irma Windy (English Education Department, Universitas Islam Indonesia, 2007)
This study focuses on analyzing the backpackers' utopianism in Alex Garland’s The Beach and the problem presented in this study is how is the backpackers’ utopianism presented in the novel. The study intends to identify utopianism that exist in the backpackers' community. The writers hopes that this study can give contribution to those interested in further analyzing the novel. In this case, the library research is used and the objective theory is employed as the basic principal of the analysis.Having a desire to find and experience something unusual and different through travel is what drives many young western backpackers to Thailand with adventure on their mind. Unfortunately what they find is no more than just a dirty reality of many overrun tourist resorts instead of a tourist free tropical paradise they long. Existing among those popularized tourist resorts is apparently, the beach, known for its beauty and natural purity. The beach happens to be an improbable tale among backpackers and travelers. However, for some other backpackers, this beach does exist. Guided by quite a top secret map, three backpackers find their pristine beach on an unspoiled island of Thailand. Once there, they are convinced that they have discovered Eden, or at least their very own version of it. Wearied by many overrun tourist spots, and impressed by the beauty of foe beach, those backpackers decide to live on the beach area eternally and secretly. In, this secret community, those backpackers adapt to foe needs and pleasures of alternatives. Unfortunately those backpackers supposedly ideal beach life is unable to be perfectly realize due to the imperfection that they find there, or more to the point, the imperfections they find within themselves.After, studying the backpackers utopianism, the writer can conclude that the backpackers’ notion of perfection upon an ideal place is in fact normal for it suggest the nature of humans as an imaginative creatures endowed with desire for perfection, especially reaction to their imperfect world. Aside from that, humans are, at the same time, likely to be considered absurd for being utopians those appear to be too exigent in demanding their particular version of ideal and thus, being less aware of the impracticability of his ideal. It is therefore to say that humans need to be sensible in idealizing their dreams. They must have complete knowledge and awareness of their own capability instead of blind faith.